Nursing Volunteering: Student satisfaction in a Teaching Hospital during the pandemic. - Berduc, Alan; Martínez, Irma; Mariano, Marcela; Sanabria, María (Spanish Journal of Medical Education, 2023)
In Argentina, on March 20, 2020, the "social, preventive and mandatory isolation" and the cessation of face-to-face educational activities are installed. With the aim of dealing with the pandemic, the Hospital launches a volunteering proposal for students of Nursing careers, interrelating an educational institution and a health institution. Before the pandemic, nursing students could not attend health institutions as volunteers, but instead did so as part of their professional practices. The general objective was to determine the degree of satisfaction of the nursing students who volunteered at the Hospital Escuela during the pandemic. A descriptive cross-sectional observational study was carried out where data was collected through a survey as a research method. A total of 376 responses were collected and analyzed. The results of the analysis allow elucidating the satisfaction of the volunteers in the sample in the three dimensions, those related to the organization, with the infrastructure where they volunteered and with the teaching-learning process. 95.4% of the students valued the experience as positive and would recommend volunteering. We must highlight as important the learning acquired, the experience, knowing the labor reality and the motivation to continue developing the activity.